Od analizy dramatu do filozofii teatru: O pracach teatrologicznych Ireny Sławińskiej - Wojciech Kaczmarek (Pamiętnik Teatralny, 2023)
This article presents the theater scholarship of Irena Sławińska (1913–2004), an eminent humanist affiliated with the Catholic University of Lublin for more than five decades, co-founder of Polish drama and theater studies. The author discusses Sławińska’s research on the language of drama, poetic and religious drama, as well as her methodological proposals for drama and theater analysis, anthropology, and philosophy. The article also describes the scholar’s role in developing relations between Polish and Western theatre studies, especially with regard to Anglo- and Francophone research, and highlights her original contribution to the analysis of anthropological foundations of the idea of theater that refers to classical philosophy and Christianity.